2005
DOI: 10.1029/2004jd005401
|View full text |Cite
|
Sign up to set email alerts
|

Radiative influences on drop and cloud condensation nuclei equilibrium in stratocumulus

Abstract: [1] Radiative heating and cooling occurs throughout most of a stratocumulus cloud layer. Shortwave (SW) heating of individual drops can be strong enough that drop temperatures at equilibrium deviate by as much as 6°C from the surrounding environment. These large temperature differences lead to substantial errors when the classical equation for vapor growth is used. A new form of the vapor growth equation is derived for cases of strong radiative heating. The new equation is used to assess the equilibrium supers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Marquis and Harrington (2005) pointed out that radiative heating and cooling rates for cloud droplets can vary by 2 to −15 K h -1 , depending on radiative fluxes, droplet diameter and droplet location with reference to cloud top and cloud base. Since the reported measurement flight was conducted between 16:30 and 17:45 CET strong shortwave heating can be neglected.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Marquis and Harrington (2005) pointed out that radiative heating and cooling rates for cloud droplets can vary by 2 to −15 K h -1 , depending on radiative fluxes, droplet diameter and droplet location with reference to cloud top and cloud base. Since the reported measurement flight was conducted between 16:30 and 17:45 CET strong shortwave heating can be neglected.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Harrington et al (2000) and Marquis and Harrington (2005) showed that thermal emission enhanced cloud droplet growth by diffusion. An earlier onset of collision and coalescence of cloud droplets was found by Hartman and Harrington (2005a, b) when thermal radiation was considered.…”
Section: Introductionmentioning
confidence: 99%
“…9 and 10 demonstrate the effect of LW radiant emission in enhancing cloud droplet growth, the opposite effect of SW (solar) radiant absorption could be shown by including it [24][25][26] in the radiation term Q r D, with the possibility that SW radiation could change the sign from negative to positive. This would require estimating absorption of SW radiation, which is more complicated just by the stronger spectral variation of water's absorption coefficient in the SW range compared to the LW range and the smaller absorption efficiency for SW radiation compared with the near unity emission efficiency for LW radiation (different absorption and emission efficiencies would need to be evaluated, as noted previously).…”
Section: Sample Cloud Droplet Radiation Calculationmentioning
confidence: 96%